Hydration-mediated co-assembly enables whole-component utilization of flaxseed - Yanwen Sun; Xiangyang Liu; Xinyue Liu; Wanjun Han; Wei Yang; Yuanfa Liu (Food Hydrocolloids, 2026)

Inhalation toxicity assessment of imidazolium ionic liquids by a physiology-based high-throughput lung-burden computational model - Wanjun Zhang; Yizhe Wu; Jiayin Sun; Jianzhong Zhang; Fene Gao; Xin Li; Wenjia Lai; Bo Li; Jing Liu; Jinglong Tang (Journal of Hazardous Materials, 2026)

Non-stationary evolution of summer wet-bulb temperature in China (1951–2024): Accelerated warming and time-varying roles of temperature and humidity - Tianci Yao; Shengfa Li; Qing Yu; Jia Sun; Xiangyu Wang; Wanjun Zhang; Lixin Su (Atmospheric Research, 2026)

Revisiting collapse sinkholes in urban loess roads affected by dynamic seepage: Theoretical and numerical investigations - Kuan Liu; Xueyang Sun; Wanjun Ye; Xi'an Li; Li Wang; Faning Dang; Paraskevas Tsangaratos; Ioanna Ilia; Wei Chen (Soil Dynamics and Earthquake Engineering, 2026)

Amphiregulin as a central dynamic network biomarker in inhaled polyhexamethylene guanidine triggered pulmonary fibrosis - Jianzhong Zhang; Xin Li; Yuxin Ma; Wanjun Zhang; Zihao Han; Yanting Li; Jiayin Sun; Siqi Wang; Wei Han; Jing Liu; Yuxin Zheng; Jinglong Tang (Journal of Hazardous Materials, 2026)

The dynamic material flow of synthetic diamond in China for 1999-2022 - Wanjun Wang; Jingyi Cheng; Qianglei Hou; Zhaoda Sun; Lijuan Li; Kewen Lyu; Changhong Miao (Resources, Conservation and Recycling, 2026)

Ultrasonic enhancement of coalbed permeability: Frequency-dependent spatial differentiation remodeling of pore to fracture - Peng Liu; Wanjun Chen; Baisheng Nie; Hao Xu; Jingtao Yang; Zhengduo Zhao; Yulong Zhao; Liang Sun; Wei Liu (Fuel, 2026)

Effects of ABC transporter polymorphism on the pharmacokinetics of pentoxifylline and its active metabolites in healthy Chinese subjects - Lingfang Guo; Xue Sun; Bo Qiu; Wanjun Bai; Yabin Du; Haojing Song (European Journal of Clinical Pharmacology, 2026)

Dynamic pro-infiltration triggers collapse sinkholes in urban loess roads: Insights from physical and numerical modeling - Kuan Liu; Wanjun Ye; Xueyang Sun; Faning Dang; Mingming He; Xu Duan; Li Wang; Jingjing Nan; Jingyun Gui; Xusheng Yan (Bulletin of Engineering Geology and the Environment, 2026)

Multiband bipolar photoresponse in Cu@CuOx@a-Ga2O3 core-shell heterostructure-based self-powered photoelectrochemical-type photodetector for secure underwater optical communication - Yixin Sun; Yan Tang; Xiuhong Jiang; Aijiang Yan; Jin Zhao; Yuchuan Wang; Jiangshuai Luo; Jili Jiang; Ke Ding; Hong Zhang; Honglin Li; Di Pang; et al. (Chemical Engineering Journal, 2025)

Synergistic interaction between hydrophilic polyglycerol fatty acid esters and sucrose esters regulates fat crystallization at the water/oil interface in highly unsaturated whipped emulsions - Wanjun Han; Yiqiu Deng; Yiting Lin; Farah Zaaboul; Qiuling Huangfu; Yanwen Sun; Xiuhang Chai; Chin-Ping Tan; Yuanfa Liu (Chemical Engineering Journal, 2025)

Multifunctional knitted fabrics based on nylon 11 and all-DNA double helix piezoelectric yarns for sensing over wide temperature range - Wanjun Bu; Qiushi Wang; Tong Lu; Mengqi Tian; Runjun Sun (Chemical Engineering Journal, 2025)

Synergistic antinematodal effects of fluopyram combined with chlorfenapyr and its potential mechanism against Bursaphelenchus xylophilus - Wanjun Zhang; Guohong Sun; Xianxiu Hu; Hao Cheng; Tingting Chen; Anshun Ni; Fang Tang; Jianren Ye (Pesticide Biochemistry and Physiology, 2025)

ZmPRR37-ZmYSL14 module enhances salt stress tolerance in maize - Zhixue Liu; Wanjun Zhang; Jing Zhang; Qi Cheng; Jiachen Liang; Chongyu Sun; Jifei Ren; Shifang Zhao; Fan Wu; Jia Shi; Huihui Su; Yanhui Chen; et al. (Theoretical and Applied Genetics, 2025)

Electrostatic self-assembly assisted construction of MXene/MoO3 hybrid aerogel for free-standing supercapacitor electrodes - Feitian Ran; Bowen Tan; Meijie Hu; Shulin Deng; Kai Wang; Wanjun Sun; Jifei Liu; Xiaobin Yang (Chemical Engineering Journal, 2025)

Muti-Biomarker Approach and IBR Index to Evaluate the Oxidative Stress of Nanoplastic on the Clams, Meretrix meretrix and Sinonovacula constricta - Linlan Lv; Wanjun Feng; Ke Sun; Weihong Zhao; Fengjuan Jiang; Mohsen Mohamed; Lei Li; Yue Yang; Yingying Zhang; Yanming Sui; Xuexing Dong (Journal of Ocean University of China, 2025)

Pulmonary surfactant biogenesis blockage mediated polyhexamethylene guanidine disinfectant induced pulmonary fibrosis - Xin Li; Jianzhong Zhang; Mingyue Wang; Haonan Li; Wanjun Zhang; Jiayin Sun; Lin Zhang; Yuxin Zheng; Jing Liu; Jinglong Tang (Journal of Hazardous Materials, 2024)

Revealing the mechanisms of water permeability enhancement of urban loess subgrades due to vibration application - Kuan Liu; Wanjun Ye; Xueyang Sun; Faning Dang; Mingming He; Zhao Duan; Jianquan Ma; Jingjing Nan; Ruihui Zheng; Quanjiu Wang (Transportation Geotechnics, 2024)

Rapid analysis of Bacillus cereus spore biomarkers based on porous channel cuttlebone SERS substrate - Yuping Lai; Guangzheng Jiang; Tianhang Liang; Xiaoxin Huang; Wanjun Jiang; Wenhui Xu; Ruikun Sun; Zhenqing Dai; Chengyong Li (Analytica Chimica Acta, 2024)

Mechanism of antibiotic resistance spread during sub-lethal ozonation of antibiotic-resistant bacteria with different resistance targets - Conglin Bai; Yiwei Cai; Tong Sun; Guiying Li; Wanjun Wang; Po Keung Wong; Taicheng An (Water Research, 2024)

The impact of natural resource extensive on green economic growth policies - WeiJin Cheng; Azer Dilanchiev; Elshan Mammadov; Sun Wanjun (Resources Policy, 2024)

Synergistic effect of hydrophilic polyglycerol fatty acid esters and protein on the stability of interfacial membrane in low-fat aerated emulsions with different homogenization conditions - Wanjun Han; Xiuhang Chai; Farah Zaaboul; Yanwen Sun; Chin-Ping Tan; Yuanfa Liu (Food Chemistry, 2024)

Different hydrophilic polyglycerol fatty acid esters interact with fat crystals and proteins at the interface to co-stabilize highly unsaturated whipped emulsions - Wanjun Han; Xiuhang Chai; Yanwen Sun; Farah Zaaboul; Chin-Ping Tan; Yuanfa Liu (Food Hydrocolloids, 2024)

Mutation of a highly conserved amino acid in RPM1 causes leaf yellowing and premature senescence in wheat - Wenjia Zhang; Zhaoheng Zhang; Qian Chen; Zihao Wang; Wanjun Song; Kai Yang; Mingming Xin; Zhaorong Hu; Jie Liu; Huiru Peng; Jinsheng Lai; Weilong Guo; et al. (Theoretical and Applied Genetics, 2023)

Effect of different chain lengths of monoglyceride on the O/W interfacial properties with high-melting and low-melting crystals in low-fat aerated emulsion - Wanjun Han; Xiuhang Chai; Farah Zaaboul; Yanwen Sun; Chin-Ping Tan; Yuanfa Liu (Food Chemistry, 2023)

Realigning the melon chains in carbon nitride by rubidium ions to promote photo-reductive activities for hydrogen evolution and environmental remediation - Yangsen Xu; Wenwu Shi; Yunxiao Zhang; Zhenlong Tu; Bangjin Sun; Zhiguo Wang; Xinzhong Wang; Zhenni Liu; Wanjun Wang (Journal of Hazardous Materials, 2023)

Pickering emulsions stabilized by hemp protein nanoparticles: Tuning the emulsion characteristics by adjusting anti-solvent precipitation - Yanwen Sun; Xiuhang Chai; Wanjun Han; Zaaboul Farah; Tian Tian; Yong-Jiang Xu; Yuanfa Liu (Food Hydrocolloids, 2023)

The decreased expression of GW2 homologous genes contributed to the increased grain width and thousand‑grain weight in wheat-Dasypyrum villosum 6VS·6DL translocation lines - Zhiyu Feng; Long Song; Wanjun Song; Zhongqi Qi; Jun Yuan; Run Li; Haiming Han; Huifang Wang; Zhaoyan Chen; Weilong Guo; Mingming Xin; Jie Liu; et al. (Theoretical and Applied Genetics, 2021)

Pleiotropic function of the SQUAMOSA PROMOTER-BINDING PROTEIN-LIKE gene TaSPL14 in wheat plant architecture - Jie Cao; Kaiye Liu; Wanjun Song; Jianing Zhang; Yingyin Yao; Mingming Xin; Zhaorong Hu; Huiru Peng; Zhongfu Ni; Qixin Sun; Jinkun Du (Planta, 2021)
Main conclusion The function of SQUAMOSA PROMOTER-BINDING PROTEIN-BOX gene TaSPL14 in wheat is similar to that of OsSPL14 in rice in regulating plant height, panicle length, spikelet number, and thousand-grain weight of wheat, but differs during tiller development. TaSPL14 may regulate spike development via ethylene-response gene EIN3-LIKE 1 ( TaEIL1 ), ETHYLENE-RESPONSIVE TRANSCRIPTION FACTOR 2.11 ( TaRAP2.11 ), and ETHYLENE-RESPONSIVE TRANSCRIPTION FACTOR 1 ( TaERF1 ), but not DENSE AND ERECT PANICLE 1 ( TaDEP1 ) in wheat. Abstract The SQUAMOSA PROMOTER-BINDING PROTEIN-LIKE gene OsSPL14 from rice is considered to be a major determinant of ideal plant architecture consisting of few unproductive tillers, more grains per spike, and high resistance of stems to lodging. However, the function of its orthologous gene, TaSPL14 , in wheat is unknown. Here, we reported the functional similarities and differences between TaSPL14 and OsSPL14 . Similar to OsSPL14 knock-outs in rice, wheat TaSPL14 knock-out plants exhibited decreased plant height, panicle length, spikelet number, and thousand-grain weight. In contrast to OsSPL14 , however, TaSPL14 did not affect tiller number. Transcriptome analysis revealed that the expression of genes related to ethylene response was significantly decreased in young spikes of TaSPL14 knock-out lines as compared with wild type. TaSPL14 directly binds to the promoters of the ethylene-response genes TaEIL1 , TaRAP2.11, and TaERF1, and promotes their expression, suggesting that TaSPL14 might regulate wheat spike development via the ethylene-response pathway. The elucidation of TaSPL14 will contribute to understanding of the molecular mechanisms that underlie wheat plant architecture.

Involvement of ROS/NLRP3 Inflammasome Signaling Pathway in Doxorubicin-Induced Cardiotoxicity - Shanshan Wei; Wanjun Ma; Xiaohui Li; Chuanhao Jiang; Taoli Sun; Yuanjian Li; Bikui Zhang; Wenqun Li (Cardiovascular Toxicology, 2020)

Flavonoid compounds and antibacterial mechanisms of different parts of white guava ( Psidium guajava L. cv. Pearl) - Wanjun Zhang; Jingyi Wang; Yashu Chen; Hongbin Zheng; Bijun Xie; Zhida Sun (Natural Product Research, 2020)

Use of near-isogenic lines to precisely map and validate a major QTL for grain weight on chromosome 4AL in bread wheat (Triticum aestivum L.) - Panfeng Guan; Na Di; Qing Mu; Xueyi Shen; Yongfa Wang; Xiaobo Wang; Kuohai Yu; Wanjun Song; Yongming Chen; Mingming Xin; Zhaorong Hu; Weilong Guo; et al. (Theoretical and Applied Genetics, 2019)

Altered splenic miRNA expression profile in H1N1 swine influenza - Liangzong Huang; Jun Ma; Yankuo Sun; Yanli Lv; Wen Lin; Mingjie Liu; Changsong Tu; Pei Zhou; Wanjun Gu; Shuo Su; Guihong Zhang (Archives of Virology, 2015)

Microbiological Identification and Analysis of Swine Lungs Collected from Carcasses in Swine Farms, China - Yunfeng Zha; Jiexiong Xie; Ye Chen; Chunya Wei; Wanjun Zhu; Jidang Chen; Haitao Qi; Liangquan Zhang; Long Sun; Xiaozhan Zhang; Pei Zhou; Zhenpeng Cao; et al. (Indian Journal of Microbiology, 2013)

Mutagenesis analysis of porcine reproductive and respiratory syndrome virus nonstructural protein 7 - Minze Zhang; Zhenpeng Cao; Jiexiong Xie; Wanjun Zhu; Pei Zhou; Honglang Gu; Long Sun; Shuo Su; Guihong Zhang (Virus Genes, 2013)

Characterization and expression pattern analysis of DcNAC gene in somatic embryos of Dendrobium candidum Wall Ex Lindl. - Peng Zhao; Wanjun Wang; Mengxiang Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)